2020
DOI: 10.1111/ajo.13127
|View full text |Cite
|
Sign up to set email alerts
|

Third‐ and fourth‐degree tears: A review of the current evidence for prevention and management

Abstract: Background: Third-and fourth-degree tears are associated with significant pain, discomfort and impact on quality of life and intimate relationships. Australian women experience comparatively higher rates of third-and fourth-degree tears relative to countries of similar economic development. Aims:We aimed to conduct a comprehensive review of the literature, published over the past five years, to identify the best ways to prevent and manage third-and fourth-degree perineal tears in Australian maternity centres. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
(56 reference statements)
3
21
1
6
Order By: Relevance
“…The induction of labor is also associated with an increased risk of severe tearing. Wilson et al [17] in a review with an N of more than 400,000 women, presented a very similar risk of third and fourth degree tears (OR = 1.08; p = 0.01) to the result presented in our study (OR = 1.29; p = 0.047).…”
Section: Discussionsupporting
confidence: 85%
“…The induction of labor is also associated with an increased risk of severe tearing. Wilson et al [17] in a review with an N of more than 400,000 women, presented a very similar risk of third and fourth degree tears (OR = 1.08; p = 0.01) to the result presented in our study (OR = 1.29; p = 0.047).…”
Section: Discussionsupporting
confidence: 85%
“…Our study affirms maternal and obstetric characteristics associated with OASIS noted in previous work, including race/ethnicity, age, episiotomy, operative delivery, and shoulder dystocia. 1 2 4 5 6 7 8 Unlike prior studies, 7 high infant birth weight was not associated with OASIS in our sample; this may reflect increasing rates of cesarean delivery in cases of suspected macrosomia or other indicators of a difficult vaginal delivery. 27 The finding that women with OASIS were at increased risk of accidental stool loss at 1-month postpartum is consistent with prior literature.…”
Section: Discussioncontrasting
confidence: 81%
“…A robust body of research has identified risk factors for OASIS which include nulliparity, operative vaginal delivery, routine use of episiotomy, higher fetal birth weight, shoulder dystocia, labor induction and augmentation, and use of epidural analgesia. 1,2,[4][5][6][7][8] OASIS was previously examined as an obstetric quality measure but ultimately eliminated, as several risk factors for severe lacerations are not modifiable. Additionally, avoiding one of the key risk factors, operative vaginal delivery, may increase cesarean delivery.…”
mentioning
confidence: 99%
“…It can be emphasized that episiotomy has an even lower statistical risk for severe perineal injury than primiparity, large birth weight, or instrumental delivery. 5 We also dispute that this study's findings suggested that episiotomy was required in a small minority of vaginal deliveries. It showed only that they occurred in a small minority of vaginal deliveries.…”
mentioning
confidence: 71%